2016
DOI: 10.1111/cogs.12349
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond Input Quantity: Wh‐Questions Matter for Toddlers' Language and Cognitive Development

Abstract: There are clear associations between the overall quantity of input children are exposed to and their vocabulary acquisition. However, by uncovering specific features of the input that matter, we can better understand the mechanisms involved in vocabulary learning. We examine whether exposure to wh-questions, a challenging quality of the communicative input, is associated with toddlers' vocabulary and later verbal reasoning skills in a sample of low-income, African-American fathers and their 24-month-old childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(147 citation statements)
references
References 60 publications
11
128
3
5
Order By: Relevance
“…Proposals for why output would have a general benefit for children's language growth include the suggestions that the requirement to talk challenges children and prods them to figure out the parts of the linguistic system they need to produce replies (Hoff‐Ginsberg, , , ; Rowe et al., ), and that talking “forces the learner to process the language in a way that only hearing it does not” (Bohman et al., , p. 339). Perhaps output also benefits language learning because output is essentially retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposals for why output would have a general benefit for children's language growth include the suggestions that the requirement to talk challenges children and prods them to figure out the parts of the linguistic system they need to produce replies (Hoff‐Ginsberg, , , ; Rowe et al., ), and that talking “forces the learner to process the language in a way that only hearing it does not” (Bohman et al., , p. 339). Perhaps output also benefits language learning because output is essentially retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on first language acquisition includes many findings that are consistent with the hypothesis that output plays a role in language acquisition: The frequency with which adults pose certain types of questions that elicit talk from children is positively associated with children's language growth (Hoff‐Ginsberg, , , ; Rowe, Leech, & Cabrera, ). The number of conversational turns in adult–child interaction, recorded and analyzed using the LENA system (Xu, Yapanel, & Gray, ), is a better predictor of children's later scores on an omnibus measure of language skills than the amount of talk produced within the child's range of hearing (Zimmerman et al., ).…”
mentioning
confidence: 80%
“…However, variation in input quality also has a role. Several indicators of quality, including lexical diversity, use of decontextualized language, and properties of verbal and nonverbal interaction are also important [55][56][57], with computational modeling showing that some quality indicators, such as lexical diversity, are more important than input quantity [58].…”
Section: Relationships Between Language and The Environmentmentioning
confidence: 99%
“…Prior analyses of the current sample showed that maternal vocabulary at 6 months and change in maternal vocabulary between 6 and 15 months each independently predicted child cognitive ability at 15 months (Burchinal, Vernon‐Feagans, Cox, & Key Family Life Project Investigators, ). In another sample, parent use of wh‐questions during a play session at 24 months was positively associated with children's reasoning skills at 36 months (Rowe, Leech, & Cabrera, ). Maternal language input has also been associated with children's theory of mind (de Rosnay & Hughes, ), including a study in which maternal use of words relating to mental states (e.g., think, believe) in a sample of children between 2 and 4 years of age was associated with theory of mind 12 months later (Ruffman, Slade, & Crowe, ).…”
Section: Ses Maternal Linguistic Input and Child Vocabulary Developmentioning
confidence: 99%